Demonstration of Schottky barrier diode integrated in 200 V power p-GaN HEMTs technology with robust stability. (July 2022) - Gallardo, Jethro Oroceo; Dash, Sachidananda; Tran, Thanh Nga; Huang, Zhen-Hong; Tang, Shun-Wei; Wellekens, Dirk; Bakeroot, Benoit; Syshchyk, Olga; De Jaeger, Brice; Decoutere, Stefaan; Wu, Tian-Li
Abstract: Development of integration of different components with GaN-based technologies has been gaining traction in recently. Among these, diodes play important roles in GaN power ICs. For this work, a fabrication approach for integrating a Schottky barrier diode (SBD) with a p-GaN enhancement (E-mode) for 200 V switching application is demonstrated. The integrated SBD with 30-mm width shows a low forward voltage (Vf ) with more than 10A and 6A at Vac = 3 V at 25 °C and 150 °C, respectively. Additionally, the devices show a stable ON-resistance (RON ) (<20% increase) up to 200 V at 25 °C/150 °C under pulsed IV characterization and OFF-state stress, pointing out the robust stability for integrated GET-SBDs on a power p-GaN HEMT platform.